Pengembangan Malilu Sipakainge 3D melalui Metode ARCS berbasis Outdoor Learning pada Materi Fungsi Bagian Tumbuhan Meningkatkan Self-Esteem Siswa Kelas IV SDN Nglegok 02 Kabupaten Blitar - Dian Novitasari; Cindya Alfi; Mohamad Fatih (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The low internal motivation and self-esteem of students in science learning is caused by the lack of innovation in the methods and limited learning media used. The study aims to of evaluating the validity, feasibility, and improvement of students' self-esteem by using Malilu Sipakainge 3D media through the ARCS method based on outdoor learning. This research used the Research and Development (R&D) methodology, using the 4D model which consists of four main stages defining, designing, developing, and disseminating. Data were collected from various sources, including material experts, media experts, teachers, and students as participants. The material expert validation resulted 77.5%, indicating ‘valid’ classification. In contrast, the media expert validation resulted 95%, indicating ‘highly valid’ classification. This study focused on students enrolled in fourth grade with a total of 20 students, the evaluation of the results of the teacher's response to the feasibility aspect obtained a score of 100% in the “very feasible” classification. The findings of this study based on the implementation of the pre and post-test showed that students' self-esteem increased, the pre-test results 64.75% with “good” classification and the post-test results 78.5% with “very good” classification. Based on the findings of this study, it can be interpreted that the development of Malilu Sipakainge 3D media for plant part function material can increase students' self-esteem.